(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In linguistics there are number of researchers devoted to verbs of motion in comparative aspect. In these researchers functioning of motion verbs in different contexts were given. Verbs of motion are classified according to grammar semantics features of Turkic languages. In Kyrgyz language they are divided into several subgroups. Verbs of motion express movement in their different characteristics